Respuesta :

gmany

Answer:

x = 1

Step-by-step explanation:

[tex]f(x)=3\sqrt{x+3}-6\\\\\text{Domain:}\ x+3\geq0\to x\geq-3\\\\\text{The zero}\to f(x)=0\\\\3\sqrt{x+3}-6=0\qquad\text{add 6 to both sides}\\\\3\sqrt{x+3}=6\qquad\text{divide both sides by 3}\\\\\sqrt{x+3}=2\iff x+3=2^2\\\\x+3=4\qquad\text{subtract 3 from both sides}\\\\x=1[/tex]

Answer:

x=1

Step-by-step explanation:

Given function,

[tex]f(x)=3\sqrt{x+3}-6[/tex]

Since, the zeroes of a function are those input values for which the function gives the output zero,

So, for the zeroes of f(x),

f(x) = 0

[tex]\implies 3\sqrt{x+3}-6=0[/tex]

[tex]3\sqrt{x+3}=6[/tex]      ( Adding 6 on both sides )

[tex]\sqrt{x+3}=2[/tex]        ( Dividing both sides by 3 )

[tex]x+3=4[/tex]                ( Taking square of both sides )

[tex]x = 1[/tex]                   ( Subtracting 3 from both sides )

Hence, the zero of the given function is, x = 1.

First option is correct.